Effects of fish cage culture on macrobenthic communities in a subtropical river - NUSRAT JAHAN TANIA; M. BELAL HOSSAIN; Ahasan Habib; NAJIAH MUSA (Society for Indonesian Biodiversity, 2020)
Abstract. Tania NJ, Hossain MB, Habib, A, Musa N. 2020. Effects of fish cage culture on macrobenthic communities in a subtropical river. Biodiversitas 21: 3583-3589. The present study described the impact of freshwater fish cage culture on macrobenthic faunal assemblages in the Dakatia River, Chandpur, Bangladesh. The experimental design involved the establishment of four stations in two study sites, two stations near the culture area, and two stations away from culture area. A total of 23 macrobenthic taxa belonging to annelids, molluscs, arthropods, and other minor phyla were recorded from study sites. Oligochaetes were found to be dominant at all four stations composing 42.34% of the total macrobenthos. Pollution indicator benthic organisms i.e., Naididae (30.32%), Tubificidae (20.16%), and Chironomidae (3.54%) were found most in the cage culture area. The density of benthic macrofauna was higher (28,134 inds./m²) in the cage culture site than the non-cage culture site (4,358 inds./m²) due to high abundance of certain pollution tolerant species. However, the values of diversity indices i.e., Species Richness (SR), Shannon-Wiener (S-W) diversity (H´), Pielou’s evenness (E), and Margalef (J) were consistently higher in non-cage culture area than the cage culture area. One-way ANOVA showed no significant variation (P > 0.05) in diversity values between the sites. The results of the present study revealed effects of cage culture on the abundance, diversity, and composition of benthic macrofauna.